Total glucosides of paeony attenuates animal psoriasis induced inflammatory response through inhibiting STAT1 and STAT3 phosphorylation. (28th October 2019) - Li, Binbin; He, Shucheng; Liu, Rui; Huang, Liangliang; Liu, Ge; Wang, Ruixuan; Yang, Zhuoyue; Liu, Xinyi; Leng, Ye; Liu, Dan; Ye, Chengyu; Li, Yunman; et al.
Abstract: Ethnopharmacological relevance: Psoriasis is an immune system meditated disease, especially T cells. It disturbed many people around the world and hard to therapy. Paeonia lactiflora Pall has been used as a medicine in china for thousands of years. Recent studies found that the main component of Paeonia lactiflora Pall can alleviates the immune response in many diseases. In this study, we researched the effects and possible mechanisms of total glucosides of paeony (TGP) on animal psoriasis. Aim of the study: To study the therapeutic effects and mechanisms of TGP in 5% propranolol cream-induced psoriasis in guinea pigs and Imiquimod (IMQ) cream-induced psoriasis in mice. Materials and methods: The effect of TGP was evaluated using a psoriasis-like model of guinea pigs and mice. Ear thickness was accessed, and pathology injury was observed by H&E staining. The levels of serum IL-1β, IL-6, IL-12, IL-17, IL-23, TNF-α, and IFN-γ, skin IL-17A, IL-22 and orphan nuclear receptor (RORγt) mRNA expression, proliferating cell nuclear antigen (PCNA), total or phosphorylated signal transducers and activators of transcription (STAT1, STAT3) were determined by enzyme linked immunosorbent assays (ELISAs), real time PCR, immunohistochemical staining, and western blotting, respectively. Results: Compared with model group, TGP treatment decreased the ear thickness, improved pathology of psoriasis, alleviated IMQ-induced keratinocyte proliferation, reduced the inflammatory cytokine, and downregulated IL-17A, IL-22, and RORγt mRNA in mice. Further study indicated that TGP inhibited STAT1 and STAT3 phosphorylation in lesion skins of psoriasis-like mice. Conclusions: TGP alleviates the symptoms of psoriasis-like guinea pigs and mice, and the possible mechanism may relate to inhibit T helper 17 (TH17) cell differentiation and keratinocytes proliferation by inhibiting STAT1 and STAT3 phosphorylation. Graphical abstract: Image 1